Expression patterns of LncRNA-GAS5 and its target APOBEC3C gene through miR-103 in breast cancer patients - Kanabe, Belan O.; Ozaslan, Mehmet; Aziz, Sherwan Ahmed; Al-Attar, Mustafa S.; Kılıç, İbrahim Halil and Khailany, Rozhgar A. (Cellular and Molecular Biology, 2021)
Early diagnosis of breast cancer can increase the survivability of the patients and the patient’s quality of life. There is growing evidence demonstrating the active role of LncRNA-GAS5 and miR-103 in cancer biology. APOBEC enzymes are important players in immunity and may contribute to carcinogenesis. Mutation and expression alteration in the APOBEC gene family was found to have a strong correlation with breast cancer risk. This study aimed to evaluate the expression level of lncRNA-GAS5 and its target APOBEC3C in women with breast cancer through expression evaluation of miR-103. Moreover, the interaction between lncRNA-GAS5 and miR-103 was studied. In the present study, forty paired tumor and normal samples classified based on breast cancer subtypes and clinical features of patients were analyzed using gene expression studies. Immunohistochemical analysis of the gene products was performed to classify tumors. The RNA samples were extracted from breast tissue. Real-time PCR was conducted for APOBEC3C and Lnc-RNA GAS5 expression. In addition, miR-103a miScript Primer Assay was utilized for the expression of miR-103-5p. It was revealed that the expression level of APOBEC3C and lncRNA-GAS5 were significantly down-regulated; however, the miRNA-103 expression level was significantly up-regulated. GAS5 expression was positively correlated with APOBEC3C expression and negatively correlated with miR-103 expression. In conclusion, we observed down-regulation of APOBEC3C and LncRNA-GAS5 and up-regulation of miRNA 103 in breast cancer patients. The expression of GAS5 may provide a new potential treatment target for breast cancer. To clarify the role of these molecules in the cellular signaling pathways, further studies are required.